A balanced edge detector for aeromagnetic data - Theobaldo Jorge, Vinicius; Pomponet Oliveira, Saulo; Pham Luan, Thanh; Duong Hao, Van- (Vietnam Journal of Earth Sciences, 2023)
One of the most significant challenges in interpreting magnetic data is to mitigate the influence of the magnetization direction in the shape of the anomalies, especially when reduction to the pole fails to position them over the sources. We propose a balanced high-order filter that has low sensitivity to the direction of the resultant magnetization. We consider an edge-detector filter based on directional analytic signals of the vertically-integrated anomaly field. To ensure that anomalies from shallow and deep sources are equalized, we balance this filter with the magnitude of its two-dimensional Hilbert transform. The proposed filter is tested using aeromagnetic data from Apiaí Terrane, Southern Brazil. The enhanced map is highly correlated with the study area's NE-SW trend of geological structures. Our results highlight the importance of using the directional analytical signals, which help reduce the influence of the magnetization direction, and the balancing filters, for equalizing the signal of shallow and deep causative sources.